Penerapan Sanksi Pidana terhadap Pelaku Tindak Pidana Korupsi Ditinjau dari Perspektif Konsep Hukum Progresif - Putri, Elfirda Ade (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
This study aims to examine and analyze the application of criminal sanctions against corruption based on progressive law. This study uses a normative juridical approach with descriptive analysis. The data used was secondary data obtained through a literature study, which was then analyzed qualitatively. Based on the research, Progressive law requires the state to embrace a boundless function and use its power to tell people what they must and must not do so as to allow them to get hold of their desired affluence. Progressivism in law is a legal philosophical overview that may have the potential to realize the ideas of justice and legal certainty. This paper emphasized that progressive law basically can be used as an alternative in law enforcement, and the establishment of law should in line with this thinking.